The phosphatase CTDSPL2 promotes proliferation, invasion, metastasis and regorafenib resistance in osteosarcoma - Guannan Bai; Shaobo Zhao; Manli Zhao; Limiao Chen; Wenhao Chen (Journal of Bone Oncology)
Osteosarcoma is the most common bone malignancy in children and adolescents. Patients with metastatic and recurrent osteosarcoma have poor prognosis. Regorafenib is a multi-kinase inhibitor recommended as a complement to standard chemotherapy in the treatment of advanced osteosarcoma. The mechanisms associated with regorafenib resistance remains unclear.In this study we performed transcriptomics, proteomics and phosphorylated proteomics using regorafenib-treated osteosarcoma cell lines (MG-63, HOS-MNNG for transcriptomics, HOS-MNNG for proteomics and phosphorylated proteomics). After comprehensive multiomics and verification analyses of differentially expressed genes, essential genes for the malignancy of osteosarcoma cells were identified. The effects of essential genes on the proliferation, invasion, and migration of osteosarcoma were determined. The study also evaluated their role in the apoptosis of osteosarcoma cells. The up-regulation of essential genes was determined by immunohistochemistry assays.Using comprehensive multiomics and verification analyses we found that the CTDSPL2 gene might play a role in the malignancy and Regorafenib resistance in osteosarcoma. In vitro and clinical specimen assays demonstrated that CTDSPL2 promotes the proliferation, invasion and metastasis of osteosarcoma cells, while inhibiting tumor cell apoptosis.In conclusion CTDSPL2 was identified as an essential gene for survival of osteosarcoma cells. Knockdown of CTDSPL2 expression significantly inhibited the proliferation, invasion, and metastasis of osteosarcoma cells, suggesting that it is involved in the formation and development of osteosarcoma tumors. Our data showed that CTDSPL2 is a potential therapeutic target for patients with osteosarcoma.